Striatal GABA levels correlate with risk sensitivity in monetary loss - Kondo, Hirohito M.; Oba, Takeyuki; Ezaki, Takahiro; Kochiyama, Takanori; Shimada, Yasuhiro; Ohira, Hideki (Frontiers in Neuroscience, 2024)
Background Decision-making under risk is a common challenge. It is known that risk-taking behavior varies between contexts of reward and punishment, yet the mechanisms underlying this asymmetry in risk sensitivity remain unclear. Methods This study used a monetary task to investigate neurochemical mechanisms and brain dynamics underpinning risk sensitivity. Twenty-eight participants engaged in a task requiring selection of visual stimuli to maximize monetary gains and minimize monetary losses. We modeled participant trial-and-error processes using reinforcement learning. Results Participants with higher subjective utility parameters showed risk preference in the gain domain (r = −0.59) and risk avoidance in the loss domain (r = −0.77). Magnetic resonance spectroscopy (MRS) revealed that risk avoidance in the loss domain was associated with γ-aminobutyric acid (GABA) levels in the ventral striatum (r = −0.42), but not in the insula (r = −0.15). Using functional magnetic resonance imaging (fMRI), we tested whether risk-sensitive brain dynamics contribute to participant risky choices. Energy landscape analyses demonstrated that higher switching rates between brain states, including the striatum and insula, were correlated with risk avoidance in the loss domain (r = −0.59), a relationship not observed in the gain domain (r = −0.02). Conclusions These findings from MRS and fMRI suggest that distinct mechanisms are involved in gain/loss decision making, mediated by subcortical neurometabolite levels and brain dynamic transitions.